2020
DOI: 10.15403/jgld-813
|View full text |Cite
|
Sign up to set email alerts
|

Does Family History of Cancer Influence Undergoing Screening and Gastrointestinal Investigations?

Abstract: Background and Aims: Although a family history of cancer (FHC) can modify the lifestyle and attitudes towards participation in cancer screening programs, studies on this relationship show mixed results and vary across populations. The objectives of the study were to compare sociodemographic characteristics, history of gastrointestinal (GI) investigations and Helicobacter pylori eradication, and modifiable cancer risk factors between those with FHC and those with no FHC (NFHC), and to investigate the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Dietary habits, alcohol consumption, and smoking could be indirect markers of socioeconomic status, which has been linked to both H. pylori and gastric cancer risk (Uthman et al, 2013;Eusebi et al, 2014). Moreover, H. pylori prevalence was associated with current and former smoking in our previous research (Razuka-Ebela et al, 2020). Socioeconomic status could affect the inverse association observed between sGA and smoking, with H. pylori a potential confounding factor.…”
Section: Other Factorsmentioning
confidence: 66%
“…Dietary habits, alcohol consumption, and smoking could be indirect markers of socioeconomic status, which has been linked to both H. pylori and gastric cancer risk (Uthman et al, 2013;Eusebi et al, 2014). Moreover, H. pylori prevalence was associated with current and former smoking in our previous research (Razuka-Ebela et al, 2020). Socioeconomic status could affect the inverse association observed between sGA and smoking, with H. pylori a potential confounding factor.…”
Section: Other Factorsmentioning
confidence: 66%
“…Similarly, long-term work stress can also affect the immune function of patients, leading to weakened resistance and making the body more susceptible to Hp infection. [ 20 , 21 ] Additionally, alcohol consumption and the consumption of spicy foods, known for their high stimulation, can increase stomach acid secretion and irritate the gastric mucosa. This compromises the protective barrier of the mucosa and makes it more susceptible to Hp invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Jaroslaw Regula 1,2 Po p u l at i o n a d h e re n c e t o c a n c e r s c r e e n i n g re c om m e n d at i on s i s n ot satisfactory in many countries. Public Health organizations have struggled to find ways to improve the situation.…”
Section: To Be Screened or Not To Be…? Psyche First?mentioning
confidence: 99%
“…Research is ongoing; however, no ideal methodology has been found, so far. In this issue of the Journal of Gastrointestinal and Liver Diseases two very interesting and valuable research studies on this topic are presented [1,2].…”
Section: To Be Screened or Not To Be…? Psyche First?mentioning
confidence: 99%
See 1 more Smart Citation